Implications of productivity growth in Pakistan: an economy wide analysis - Debowicz, Darío; Dorosh, Paul A.; Robinson, Sherman; Haider, Syed Hamza (International Food Policy Research Institute, 2014)
This policy note describes the economy wide implications of public investments and policies developed under Pakistan’s new Framework for Economic Growth. Policies based on this Framework are expected to lead to substantial gains in productivity in the industrial and service sectors of Pakistan’s economy. We use Computable General Equilibrium (CGE) analysis to compare the implications on welfare and growth under different distributions of productivity growth across sectors.